Trabecular bone mass and bone formation are preserved after limb immobilisation in p53 null mice - Okazaki, R (2004)
Materials and methods: Tibias of immobilised hind limbs of p53 gene knockout (p53(-/-)) and wild-type (p53(+/+)) mice were compared. Right knee joints of 8 week old mice were immobilised in full extension for 7 days. Trabecular structure and bone formation were similar in the p53(-/-) and p53(+/+) control groups. Results: Immobilisation significantly reduced BV to 77% of the control in p53(+/+) mice, but no change was noted in p53(-/-) mice. After immobilisation, bone formation rate was significantly reduced in p53(+/+) but not in p53(-/-) mice. In bone marrow cell cultures the numbers of alkaline phosphatase positive colony forming units-fibroblastic and mineralised nodules were significantly reduced by immobilisation in p53(+/+) but not in p53(-/-) mice. Immobilisation enhanced p53 mRNA expression in marrow cells of p53(+/+) mice and increased terminal dUTP nick end labelling positive osteocytes and marrow cells in p53(+/+) but not in p53(-/-) mice. Lack of p53 in immobilised mice was associated with preservation of trabecular bone mass and bone formation and suppression of significant apoptosis of marrow cells. Conclusion: Disruption of the p53 gene preserves trabecular bone mass and leads to bone formation after limb immobilisation.